The use of biomarkers GP-73 and AFP in the early diagnosis of hepatocarcinoma associated with liver cirrhosis of HCV etiology - A. K. Bayjanov; U. Yu. Ismоilov; A. S. Khikmatullaeva; Kh. P. Nasirova; J. A. Anvarov; Ch. B. Turaeva (Журнал инфектологии)
Purpose: comparative study of the informativeness of tumor markers GP-73 and AFP in the early diagnosis of hepatocellular carcinoma associated with liver cirrhosis of HCV etiology.Materials and methods: In the study, 71 people were divided into 4 groups. The groups included patients with hepatocarcinoma, liver cirrhosis, chronic viral hepatitis C and healthy people. Healthy people made up the comparison group. In all patients, the study included the study of AFP and GP-7 protein values. Fibrotic changes in the liver tissue were studied based on the results of ultrasound and fibroscanning of the liver using the Fibroscan apparatus (France).Results. In the verification of fibrosis (cirrhosis) and tumor lesions of the liver, the threshold values for GP-73 and alpha-fetoprotein (AFP) were 529.9 ng/l and 29 ng/ml, respectively. At the same time, the level of specificity of the GP-73 marker was equal to 86%, and sensitivity – 87%. In this case, the sensitivity and specificity rates of AFP were 71% and 79%, respectively. The level of negative diagnostic value of the GP-73 marker was 86.5%, and the level of positive prognostic value of GP-73 was 85.2%, while these AFP indicators were 72.6% and 76%, respectively.Conclusion: The marker – serum protein Golgi-73 can be used as a reliable diagnostic marker for early verification of hepatocellular carcinoma associated with liver cirrhosis of HCV etiology.